Pengaruh Sosialisasi Perpajakan, Pengetahuan Perpajakan, Kualitas Pelayanan Fiskus dan Minat Penerapan E-Filling pada Kepatuhan WPOP - Pratiwi, Putu Eka Mas; Jati, I Ketut (E-Jurnal Akuntansi, 2020)
The purpose of this research is to find out the effect of socialization taxation, taxation knowledge, service quality, and behavioral intention of using E-Filing at the South Badung Pratama Tax Office. The population in this research were all taxpayers registered at the KPP South Badung. There were 100 respondents used as a sample in this research from 45.326 people who were still effective at the South Badung Pratama Tax Officer. This research instrument uses a questionary method and for data analysis techniques are used multiple linear regression analysis.    The Slovin formula with an incidental sampling technique was used to calculate the sample. The results of the research show that socialization taxation, taxation knowledge, service quality, and behavioral intention of using E-Filing are positive for the individual taxpayer tax rate. Keywords: Socialization;  Knowledge; Service Quality; E-Filling, Taxpayer Compliance.